The role of mean platelet volume/platelet count in differentiation of simple and complex febrile seizures (Annals of Medical Research, 2023)
Aim: Our study aimed to find the relationship between MPV (Mean Platelet Volume) levels, a marker of inflammation, and platelet counts between simple and complex febrile seizures.Materials and Methods: In this retrospective comparative study, we analyzed the records of 283 children between the ages of 6 months and 6 years who were diagnosed with simple and complex febrile seizures (BFN/CFN) in the Pediatric Neurology Clinic of XXX University, Faculty of Medicine between January 2021 and December 2022.Results: The mean age and gender characteristics of the patients were similar in both groups. The MPV of the CFN group (69 patients) (6.53±0.39fl) was lower than that of the BFN group (214 patients) (7.81±0.43fl) and this difference was statistically significant (p
Keywords: Febrile seizure; Platelet; Mean platelet volume